(untitled) (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Assessment of nicotine dependence among tobacco users is essential as highly dependent individuals have greater risk of developing tobacco related physical and psychiatric problems. There is little information about the tobacco use and nicotine dependence among psychiatric patients in developing countries, including Nepal. Objectives: To estimate the prevalence of tobacco use, the level of nicotine dependence and the psychiatric disorder specific prevalence among tobacco users visiting a psychiatry out-patient department. Materials and methods: A cross-sectional study was conducted in Out-patient setting of Department of Psychiatry, B. P. Koirala Institute of Health Sciences (BPKIHS). Ninety cases (calculated sample size) were enrolled. The Fagerström Test for Nicotine Dependence (FTND) was applied to assess the level of nicotine dependence and the Mini International Neuropsychiatric Interview (MINI) for diagnosis of Psychiatric disorders. Results: The prevalence of tobacco use was 55.6%. Tobacco use was more common among males (pvalue < 0.05). Smokeless form was the common form of tobacco. Majority of them had started their consumption in their adolescence. Most users had moderate nicotine dependence. Major depressive disorder and Alcohol dependence were the most common diagnoses among tobacco users. Conclusion: More than half of the psychiatry out-patients consumed tobacco. Future studies that help to understand the relationship and possible mechanism of increased tobacco use in patients with psychiatry disorders are required. Tobacco control and prevention strategies should be initiated targeting vulnerable populations such as male gender and adolescent.